Mass incarceration and neoliberal penality: a response to Lloyd and Whitehead's Kicked to the Curb - Cummins, Ian (International journal of law, crime and justice, 2020)
This paper is written in response to Lloyd and Whitehead’s (2018) Kicked to the Curb: The triangular trade of neoliberal polity, social insecurity, and penal expulsion. Using the “triangular trade” that underpinned chattel slavery as an analytical metaphor, Lloyd and Whitehead (2018) argue that the growth of mass incarceration is an endogenous feature of neoliberalism. They conclude a distinctive form of penality - neoliberal penality has developed over the past forty years. Lloyd and Whitehead (2018) propose that a tripartite model - neoliberalism, precarity and mass incarceration - as the basis for a model of neoliberal penality. This paper uses an exploration of the arguments raised by Lloyd and Whitehead (2018) to examine the links between neoliberalism and the expansion of the penal state. Whilst recognising the centrality of race to these issues, the paper argues that the model that Lloyd and Whitehead (2018) present offers a partial explanation for mass incarceration. This paper acknowledges that the triangular trade metaphor is a powerful one but will conclude that it has limitations. In particular, the comparihson between mass incarceration and chattel slavery is overstated. The economic impact of slavery and its centrality to the modern capitalism (Williams, 2014) cannot be compared to the exploitation that occurs in the current prison system. The paper argues that neoliberalism, precarity and mass incarceration are clearly linked but do not constitute a triangular trade as Lloyd and Whitehead (2018) conclude.